An investigation into conversational implicatures found in “game of thrones: season 5-6” - Phạm Kiều Duyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aimed to study the conversational implicature produced by violating the Grice’s maxims in the “Game of Thrones: season 5-6” with a discourse analysis and pragmatics. As a result, the goal of this study is to identify and evaluate violations of Grice's maxims caused by the speakers' disclosure in Game of Thrones: season 5-6”. To fulfill the goals of this study, two research questions are created about the types and reason in violating maxims. The qualitative method is utilized to achieve the research objective and find out the conversational implicatures and maxims flouted. In order to gather the data, the researcher considered human and document as the instruments. The human instrument in this research was the researcher herself who gathered, identified, and analyzed the data. The document instrument in this research was “The game of Thrones: season 5-6” movie script. After analyzing, researcher realized the utterances containing the maxim violation fall into two types: single and multiple maxim violation. The characters in the film violated all four Grice’s maxims namely, Maxim of Quantity, Quality, Relevance, and Manner. Moreover, they also violated more than one single maxim to obtain conversational purpose. Furthermore, the researchers found out the motivation of violating maxims is manufactured by the eleven reasons: to stress the statement, to be sarcastic, to express the feeling, to warn someone, to make request, to please interlocutor, avoid discussion, protract the answer and mislead the counterpart. Those findings also proved that interlocutor must be conscious of possibility of maxim violations as implicature in conversation to comprehend what speaker wants to convey